TINJAUAN PENGETAHAUAN PASIEN DENGAN MASA BERLAKU SURAT RUJUKAN BALIK PUSKESMAS AMBACANG PADANG TAHUN 2021 - Rahman, Khalilul; Yulia, Yulfa; Wisandra, Ade (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The implementation of the referral system is held with the aim of providing quality health services, so that the objectives of the service are achieved without having to incur expensive costs. The purpose of this study was to determine the relationship between patient knowledge and the validity period of a referral letter at the Ambacang Padang Health Center in 2022. This type of research was quantitative with a cross sectional research design. This research was carried out at the Ambacang Health Center in July 2022. The population in this study was 400 patients per month. While the sampling using the slovin formula amounted to 80 respondents. Data were analyzed by univariate and biavariate by using Chi-square test. The results showed that more than half (51.3%) of respondents had a low level of knowledge, more than half (67.5%) of respondents had an invalid reference letter. There is a relationship between knowledge and the validity period of the referral letter with a p-value of 0.000 (p<0.05). Based on the results of the study, it can be concluded that there is a relationship between knowledge and the validity period of the referral letter. Suggestion, Through the head of the Puskesmas in order to further increase the patient in taking medication with the community about the importance of paying attention to the referral letter that is still valid so that the community is no longer mistaken with the referral letter used and so that the community is more aware of the importance of a valid referral letter.Keywords: Knowledge, Validity Period, Reference Letter